Treatment of pigeon (Columba livia domestica) infected with Hadjelia truncate by ethanolic suspension of Calvatia craniiformis in comparison with ivermectin: Ghassan H. Jameel1, Amer M.A.AL.Amery2, Maisaa G. Taher3 and Zahid I. Mohammed4 - AL.Amery, Amer M.A. (The Iraqi Journal of Veterinary Medicine, 2017)
This study aimed at evaluating the efficacy of different concentrations of C. craniiformis mushroom suspension in pigeon flock infected by Hadjelia truncata worms in Diyala province in comparison with 0.1% ivermectin. Thirty pairs of pigeons were brought to the veterinary clinic with case history of progressive weight loss, weakness, and some birds have died suddenly. In the necropsy of 3 cases the gizzards contained some nematodes, located under the koilin layer of the gizzard, which was identified microscopically as Hadjelia truncata which was one of the important parasites of the digestive system of poultry. Three different concentrations of suspension were prepared from Calvatia craniiformis mushroom powder (0.25, 0.5 and 1mg\ml) and that tested for antiparasitic effect in comparison with ivermectin as common broad spectrum anthelimntics drug. All the concentrations of the suspension showed active effect against the parasites but, ivermectin showed a better effect.